An exploratory study of problematic shopping and problematic video gaming in adolescents - Greenberg, Norman R.; Zhai, Zu Wei; Hoff, Rani A.; Krishnan-Sarin, Suchitra; Potenza, Marc N. (PLOS ONE, 2022)
Problematic video gaming (PVG) and problematic shopping (PS) are addictive behaviors prevalent in adolescents, characterized by positive and negative reinforcement, and associated with psychosocial impairment. This study examined how PS and PVG relate in adolescents. It also examined how PS interacts with PVG in relation to health/functioning measures. Survey data from 3,657 Connecticut high-school students were evaluated. Chi-square analyses and logistic regression models were used to assess relationships between PS and measures of PVG. Interaction analyses measured effects of PS on relationships between PVG and health/functioning measures. Relative to adolescents without PS, those with PS had 8.79-fold higher odds of exhibiting PVG and were more likely to endorse gaming to relieve anxiety and impairment due to gaming. Interaction analyses revealed that in adolescents with PS, the relationships between PVG and aggressive behaviors, including fighting, serious fighting leading to physical injury, and weapon-carrying, were stronger than in adolescents without PS. PS strongly relates to PVG, and among youth reporting PS, there are stronger associations between PVG and aggressive behaviors. Prevention efforts for adolescents should consider the co-occurrence of PS and PVG. PS and PVG may be linked by negative reinforcement and propensities for aggressive and addictive behaviors, suggesting that further research should explore possible interventions targeting stress management and maladaptive coping.